The impact of housing non-cash income on the unconditional distribution of household income in Austria - Pirmin Fessler; Miriam Rehm; Lukas Tockner (European Central Bank (ECB), 2014)
We estimate non-cash income from owner occupied housing, subsidized rental housing, or free use of one's main residence and evaluate their impact on the unconditional distribution of household income and selected inequality measures. We confirm the standard finding in the literature that imputed rents accruing to home owners have an equalizing effect on the distribution of income and find similar evidence for non-cash income from subsidized rents. Whereas imputed rents equalize the upper part of the income distribution, subsidized housing has an equalizing effect on the lower part of the income distribution. Overall, the effect of non-cash income from owner occupied housing clearly dominates the distributional effects, which translates into a combined effect of around 15% higher income for the bottom half and around 10% for the upper half of the unconditional income distribution. Our data provide us with the rare opportunity to apply all three commonly used approaches to calculate imputed rents for owner occupiers: capital-, self-assessment and equivalent rent approach. We find that using the equivalent rent approach leads to the strongest reduction in income inequality.
Keywords: D12; D14; D31; 330; household main residence; housing policies; imputed rent; income distribution; non-cash income; subsidized rent